Alcohol consumption and the soberness movement of ruthenians of bukovina in their polyethnic environment in the second half of the 19th-early 20th centuries| Rezumat: Consumul de alcool și mișcarea de abstinență la rutenii din Bucovina în a doua jumătate a secolului al XIX-lea-începutul secolului XX, în context multietnic - SAVCHUK, Borys; Oliynyk, Mariya; PURICI, Ștefan; BILAVYCH, Halyna (My University, 2021)
The study considers the implications of alcohol production and use, as well as the evolution of the abstinence movement among the Ukrainian population of Bukovina in the second half of the 19th - early 20th centuries in, a polyethnic context. The authors examined the state and local authorities' policies on alcoholic beverage marketing. The reactions of the Ruthenians in Bukovina to anti-alcohol campaigns that occurred among other ethnic groups in the region are explored.
Keywords: Bukovina; alcoholism; soberness movement; anti-alcohol struggle; Ruthenians; ethnic communities